Institutional delivery and associated factors among women who gave birth in Benishangul Gumuz region, South West Ethiopia - Arega, Temesgen; Mulatu, Teshale; Alemayehu, Afework; Mussa, Ibsa; Dheresa, Merga (Frontiers in Public Health, 2022)
Background Maternal mortality from pregnancy and childbirth remains a major public health problem. Increasing access to institutional delivery is one of the key strategies to reduce childbirth-related maternal mortality. Despite all the efforts, institutional deliveries in Ethiopia remain low. Understanding factors associated with institutional delivery is important to devise strategies to improve facility based child birth. Hence, this study assessed the prevalence of institutional delivery and associated factors to bridge the gap. Methods A community-based cross-sectional study was employed from March-April 2020. Multi-stage sampling was employed to select 500 mothers who gave birth within the last 12 months in Mandura district, Benishangul Gumuz Region, Ethiopia. Data were collected using pre tested structured questionnaire through face-to-face interview. Logistic regression models were fitted to assess the predictors of institutional delivery. Adjusted Odds ratios with 95% CI was used to show associations and statistical significance was set at a p < 0.05. Results This study indicated that the prevalence of institutional delivery was 28.8% CI (25–33.3%). Having a positive attitude (AOR = 9.6,95%CI:2.5–35.9), attending antenatal care (ANC) at least once (AOR = 16.1,95%CI:9.6–22), attending ANC more than three times (AOR = 17.2, 95% CI:13.5–43.8), having good knowledge (AOR = 11.1, 95%CI: 2.7–45.4), and facing complications during pregnancy (AOR = 4.04, 95%CI: 1.0–16.0) were significantly associated with institutional delivery. Conclusion The prevalence of institutional delivery in this study was low. Positive attitude toward institutional delivery, attending ANC, having good knowledge about institutional delivery, and facing complications during pregnancy were identified predictors of institutional delivery. Strategies with a focus on increasing ANC uptake, improving mothers' knowledge, and promoting institutional delivery at the community level are critical.